Faktor Tingginya Harga Produksi Yang Menyebabkan Rendahnya Minat UMKM di Desa Tambun Sungkean, Kecamatan Onan Runggu, Kabupaten Samosir, Sumatera Utara - Indah Wahyu Prastiwi; Fahmi Reja Sitepu; Siti Aisyah; Imsar Imsar (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This research is part of the UINSU Community Service Program (KKN) held in Tambun Sungkean Village, Onan Runggu District, Samosir Regency, North Sumatra. The aim of this study was to examine the impact of high production costs on low community interest in establishing MSMEs. Field research indicates that most businesses face the challenge of high production costs, particularly those related to raw material costs, transportation costs, and labor costs. This results in less competitive product prices, reducing community interest in establishing and maintaining MSMEs. The results showed that production costs had a significant negative impact on community interest in developing MSMEs, contributing 62%. Other factors, such as limited access to capital, low consumer purchasing power, and a lack of technological support, also exacerbate the impact of high production costs. This study found that to encourage small and medium enterprises (MSMEs) in Tambun Sungkean Village, methods to reduce production costs through efficiency, making raw materials more accessible, and obtaining government support such as subsidies and business management training are crucial.